141 Team Science Training Needs and Preferences for Clinical Research Professionals: A Mixed Methods Needs Assessment - Carolynn Thomas Jones; Bernadette Capili; Jessica Fritter; Shirley Helm; Angela Mendell (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: To comprehensively understand the training needs of clinical research professionals (CRPs) employed across various roles in team science. The purpose is to identify areas for competency development and determine the modality of training desired to enhance their skills further. METHODS/STUDY POPULATION: This study targets Clinical Research Professionals (CRPs) across various roles in Academic Health Centers via an online survey. From novices to experts, participants are often trained on the job covering some clinical research competencies, but team science aspects like communication and leadership are usually overlooked. The survey will assess current skills, identify training gaps, and explore preferred learning methods and topics. Participants will be recruited through the CTSA hub research network. Additionally, they'll share experiences of team cohesion, dynamics, conflict, and their contributions to the team through participation in focus group sessions.The focus groups will be held via Zoom with volunteer participants from the survey (6 per session, 3 sessions, N=18). RESULTS/ANTICIPATED RESULTS: The recently developed leveled CRP team science competencies based on Lotrechianno (2022) will be the basis of the survey items. Demographic characteristics of the participants by role will be presented. Moreover, perceptions of team science applications, learning needs and training preferences will be described. Results will be compared across CRP roles. Finally, three recorded and transcribed focus groups (n=18) will contribute to knowledge gained through this research allowing for a deeper understanding of training needs. Qualitative analyzes of recorded focus-group discussions will present key themes. Qualitative data will be coded by more than two people for interrater reliability. DISCUSSION/SIGNIFICANCE: This study offers the first needs assessment on academic medical center CRP team science learning requirements, utilizing newly established CRP individual and team competencies. Findings will guide the creation of tailored training and research initiatives.